Therapeutic Promise of Hyaluronidase in Systemic Sclerosis: A Systematic Review - Anika Pulumati; Rachel Lin; Scott Elman (Mattioli1885, 2024)
Introduction: Systemic sclerosis, also known as scleroderma, is a chronic disease marked by autoimmune-mediated damage to connective tissues leading to vascular damage, tissue injury, and fibrosis. Effective treatment for this condition has remained difficult; however, a promising therapeutic option for patients with systemic sclerosis has emerged as hyaluronidase. Objectives: We conducted a systemic review of the available literature to describe the therapeutic usage of hyaluronidase in systemic sclerosis. Methods: We conducted a comprehensive review on PubMed and Embase, using the terms: "hyaluronidase" AND "scleroderma," as well as "hyaluronidase" AND "systemic sclerosis." Our criteria for inclusion were English-written articles published between 2013 and 2023. Only studies conducted on human subjects or in vitro on human cell lines were included. We excluded articles that did not discuss therapeutic use as well as articles that focused on medical conditions other than systemic sclerosis. Results: Ten articles were included in our review. Overall, intradermal hyaluronidase showed improvement in systemic sclerosis-associated microstomia via increased oral aperture with minimal side effects. Treatment protocol and outcome measured differed per case, however, multiple rounds of injections were necessary in all treatment courses. In some studies, a plateauing effect for hyaluronidase was seen after 3-5 months of injections. Conclusion: Case studies and case series have demonstrated hyaluronidase's effectiveness in treating systemic sclerosis-associated microstomia, however, more research using larger sample sizes, standardized protocols, and specific outcomes such be conducted.